2003
DOI: 10.2320/matertrans.44.637
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction of Sm from Sm-Co alloys by the Glass Slag Method

Abstract: The use of the glass slag method in the extraction of Sm from Sm-Co alloys was studied. The magnetic SmCo 5 phase decomposed into Sm oxide phase and Co phases by the glass slag method. The Sm oxide phase was extracted by the surrounding molten glass slag materials in the glass slag method. The resultant alloys consisted of neither SmCo 5 phase nor Sm oxide phase. In the glass slag method, the Sm-Co alloys were separated into Sm-containing glass slag material and a Co-B alloy. The glass slag method was suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…We have reported that Sm-Co alloys can be separated into Sm-containing boron trioxide and a Co-B alloy and that Sm-Fe alloys can be separated into Sm-containing boron trioxide and an Fe-B alloy by the glass slag method [9,10]. Unlike the Sm-Fe alloys, Sm-Fe-N alloy was separated into Sm-containing boron trioxide and an Fe metal by the glass slag method.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have reported that Sm-Co alloys can be separated into Sm-containing boron trioxide and a Co-B alloy and that Sm-Fe alloys can be separated into Sm-containing boron trioxide and an Fe-B alloy by the glass slag method [9,10]. Unlike the Sm-Fe alloys, Sm-Fe-N alloy was separated into Sm-containing boron trioxide and an Fe metal by the glass slag method.…”
Section: Resultsmentioning
confidence: 97%
“…Several attempts have been made to recycle rare-earth permanent magnet materials [3][4][5][6][7]. We have been studying for a dry recycling process, the so-called glass slag method, and have succeeded in the recovery of Nd from Nd-Fe-B alloys and Sm from Sm-Co and Sm-Fe alloys by this method [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that the SmCo 5 phase decomposes into the mixtures of Sm-containing phase, Co, and Co 3 B phases and that the Sm-containing phase is extracted by the surrounding molten boron trioxide in the glass slag method. 12 By the same token, the La-Ni alloys may decomposes into the mixtures of La-containing phase, Ni and Ni 3 B phases and the La-containing phase might have been extracted by the surrounding molten boron trioxide during the melting and solidification of the LaNi alloy. Therefore, the microstructural studies of the La-Ni alloy were done to evaluate the amount of the respective phases.…”
Section: Methodsmentioning
confidence: 99%
“…the extraction of Nd from scrap having an oxygen content of several percent [7]. We have been studying for another dry recycling process, the so-called glass slag method, and have succeeded in the recovery of Nd from Nd-Fe-B magnets and Sm from Sm-Co magnets by this method [8,9]. However, no systematic studies have been conducted on the relationship between the microstructures and magnetic properties of rare-earth compounds and glass slag materials.…”
Section: Introductionmentioning
confidence: 97%